The Effect of Nurses' Workload on Compliance in Implementing Patient Education Before Discharge: The Mediating Effect of Perceived Organizational Support and Burnout Level - Cornelius Danu Kurniawan; Yohana F. Cahya Palupi Meilani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Nurses are essential to delivering discharge education, which ensures safe transitions and reduces hospital readmissions. However, high workloads can hinder nurses' ability to consistently provide this education. While burnout and perceived organizational support (POS) may mediate this relationship, evidence in the Indonesian healthcare setting is limited. Objective to analyze the effect of nurse workload on compliance with discharge education and assess the mediating roles of burnout and perceived organizational support. Methods a cross-sectional quantitative study was conducted with 100 nurses at a Type B private hospital in Semarang, Indonesia. Data were collected via validated questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results Workload had a significant negative effect on compliance with discharge education and a significant positive effect on burnout. Burnout also had a strong negative effect on compliance and significantly mediated the relationship between workload and compliance. Conversely, perceived organizational support showed no significant influence on compliance and did not mediate the workload–compliance relationship. Conclusion Increased nurse workload reduces compliance with discharge education, primarily through its effect on burnout. Although nurses reported high levels of organizational support, it did not significantly impact educational compliance. Interventions focusing on workload management and burnout prevention are crucial to enhance the quality of discharge education and patient outcomes.